PELAKSANAAN GURU DALAM MENERAPKAN KETERAMPILAN MENGADAKAN VARIASI PADA PEMBELAJARAN IPS DI SMP NEGERI 3 PANTAI CERMIN KABUPATEN SOLOK - Rengga, Novma; Zafri, Zafri; Kaksim, Kaksim (Pendidikan Sejarah, 2014)
This study aimed to describe the ability of a social studies teacher held variation in applying skills in the learning process in the history of SMP Negeri 3 Mirror Beach, Solok. This type of research used in this study is the evaluation of research studies with qualitative analysis to study the location of SMP N 3. Based on these results it can be concluded that the implementation of teachers skills in applying variations on pebelajaran IPS held at SMP Negeri 3 Coast Mirror both variations in the way of teaching styles, use of media and learning tools, as well as patterns of interaction in the classroom has not been implemented to the maximum. Teachers should be able to apply ketermpilan held variations on each learning process takes place.